CONCEPT AND METHODOLOGY OF JOB ORDER COSTING THEORY AND PRACTICE - Mela Zahrani; Amanda Enggelia Purba; Farhan Hilal; Mariana Mariana; Diana Diana (Prodi Hukum Ekonomi Syariah, STI Syariah AL-Hilal SIgli, 2025)
The concept and methodology of job order costing will be discussed in this article. As mentioned above, job order costing is a cost accounting method used by manufacturing companies to calculate and allocate production costs based on specific orders provided by customers. Job order costing is an ideal method if the product is unique and non-standard, which is usually the case in the construction, printing and private project sectors. Job order costing involves the collection of raw material costs, direct labor costs, and factory overhead costs which are aggregated and accumulated into separate accounts at order turnover. Once the order is completed, these costs should be reduced to the actual production account and accumulated if necessary. The generated order costing cost report is an important tool for analyzing profitability and decision making, which performs pricing and controls overproduction and unproductivity. Although this is the most accurate costing method, the first, most detailed cost accumulation, and often complex salvos. Innovation and technology, including accounting software, have also improved and increased the cost of audit work.